Training and Practice: Making the Match – Teacher training for CLIL at ELTE Faculty of Primary and Pre-School Education (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2017)
CLIL module for kindergarten teachers was introduced in 2006 at ELTE Faculty of Primary and Pre-School Education, Budapest. For primary teacher trainees, a similar programme was launched a year later. While the kindergarten programme included two one-week-long practice periods in kindergarten, this opportunity was not made available for primary trainees. In order to make up for this shortfall, two tutors of the Department (the authors of the present study) developed and implemented a system according to which each primary teacher trainee can observe CLIL lessons as well as participate in post-lesson discussions in CLIL institutions. The article intends to introduce the CLIL training, the partner institutions and their English language programmes as well as share trainees’ feedback concerning the benefits they gained from these school visits.